Derechos iniciales de propiedad y eficiencia: un problema para el análisis económico del derecho normativo (2005)
Within the scope of the Economical Analysis of Law, it has been expounded that efficiency constitutes or rather, could plausibly constitute the basis of the legal system and institutions. This article examines the problems that face the most frequent normative criteria of Normative Economics in general, and the Economical Analysis of Law in particular, in order to found property tights at initial conditions: rights that all in all, have not yet been an object to transactions